Diversity and ecological role of macro insects on cultivated chili pepper using barrier crops - Sataral, Mihwan; Palebang, Melcyani; Qodri, Agmal (Comunicata Scientiae, 2023)
Habitat manipulation by planting plants in the land or around crops is a way to increase the diversity of insects. The homogeneity of the agricultural landscapes leads to a decrease in insect biodiversity and ecosystem services. This study focuses on examining the diversity and ecological role of macro insects in chili pepper using barrier crops. We use mung beans, tomatoes, and eggplant as a barrier crops in the practice of cultivating chili pepper. The results showed that the use of barrier crops is not significant to increase the diversity of insects but the use of mung bean barrier can increase the number of species. Chili pepper land with mung bean barrier shows the abundance of predators, parasitoids, and pollinators higher than land without barrier crops. On land without barrier crops, the composition of herbivore insects tends to be lower when compared to land using barrier crops. The number of natural enemy individuals (predators and parasitoids) on land with mung bean barrier tend to be higher compared to without barrier crops. In the practice of chili pepper cultivation, it is necessary to utilize mung beans as a barrier for pest management strategy and increased production of chili pepper and also for conservation strategy of natural enemies